Grid connected mega-watt range solar power plant in India: experimental measurement & performance analysis - J. Raja; Nishant Jain; C. Christober Asir Rajan (International Journal of Applied Power Engineering (IJAPE), 2019)
in India to meet its future energy demand. This paper emphasis on the performance assessment of grid connected mega-watt solar power plant which is of 23MW and 5MW are located in different geographical location in India. Performance assessment is the finest way to determine the potential of energy generation in solar power plant and it also helps in evaluating the design, operation and maintenance of existing and future solar power plant. The parameters namely calculation of annual energy generated, reference yield, final yield, system losses, cell temperature losses, performance ratio and capacity utilization factor are considered in examining solar power plant performance. In this study experimental measurement of two solar power plant one is located in Gujarat (23MW) and another in Andhra Pradesh (5MW) are compared with the results of estimated model from METEONORM 7.1 and PVSYST V6.67 software tools. Experimental measurement at solar power plant location covers the following measurement for analysis like actual weather condition, daily/hourly irradiance, actual energy yield and compares with capacity utilization factor, performance ratio and temperature corrected performance ratio parameters. The results demonstrated in this paper show the gap between the actual performance of solar power plant and the estimated model from software tool. Performance of solar power plant is satisfactory in comparison with other literature reviews. The actual annual energy generated for 23MW solar power plant was 37991MWh, 18.83% capacity utilization factor, 73.87% performance ratio and 75.33% temperature corrected performance ratio. Similarly, the actual annual energy generated for 5MW solar power plant was 9047.7MWh, 18.41% capacity utilization factor, 80.31% performance ratio and 79.90% temperature corrected performance ratio.